1962
DOI: 10.1037/h0083238
|View full text |Cite
|
Sign up to set email alerts
|

Semantic satiation in an addition task.

Abstract: S repeated a digit aloud for 15 sec. before adding 2 single-digit numbers presented in sequence. When the repeated digit was the same as one of those added, solution time was greater as predicted. It was assumed that the increased latencies resulted from reductions in the meanings of the mathematical symbols. With practice there was a steady increase in the experimental latencies, while control latencies decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

1962
1962
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
2
13
1
Order By: Relevance
“…It would seem, therefore, that it is not an appropriate control in comparison with the Satiation condition and other controls, none of which involves a rapid switch in stimuli to be rated. In cases where one is mainly interested in the effect of such a switch on encoding and decoding procesaes (as was the case in the bilingual study of Jakobovits & Lambert, 1962), the procedure is appropriate and particularly valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would seem, therefore, that it is not an appropriate control in comparison with the Satiation condition and other controls, none of which involves a rapid switch in stimuli to be rated. In cases where one is mainly interested in the effect of such a switch on encoding and decoding procesaes (as was the case in the bilingual study of Jakobovits & Lambert, 1962), the procedure is appropriate and particularly valuable.…”
Section: Discussionmentioning
confidence: 99%
“…One purpose of the present study was to examine its effectiveness as a method of differentiating the distinctive features of numbers as well as words. In a recent study, Jakobovits & Lambert (1962) argued that the meaning of numbers could be reduced through their continuous use, much as the meaning of words can be satiated (Lambert & Jakobovits, 1960). It was demonstrated that continuous verbal repetition of a number such as ' 7 ' prior to its occurrence in a simple addition problem ( 7 + 4 = 2) increased the time taken to add.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, (Jakobovits and Lambert, 1962a) using the verbal repetition procedure with digits as stimuli, evidence was obtained of an increase in the latency of solution of computational tasks which involve satiated digits. Such findings, according to the authors, may be considered analogous to the decrease of semantic ratings of words after their continuous repetition.…”
Section: The Phenomenon Of Semantic Satiationmentioning
confidence: 99%
“…Such a phenomenon is of interest because it suggests that the lexical or semantic representation of a word is susceptible to fatigue through continuous activation, thus slowing any cognitive operations that rely on the word's meaning. For example, in one experiment it was found that continuous repetition of the number 7 prior to adding 7 + 7 increases response time compared to a condition of repeating the number I (Jakabovitz & Lambert, 1962). In general, if awareness of a word's meaning can be equated with activating the underlying semantic representation, then any measure of decrement in meaning that is used to monitor the extent of lexical fatigue would, in effect, also be measuring the extent of semantic satiation.…”
mentioning
confidence: 99%